Double-coated Si-based composite composed with carbon layer and graphene sheets with void spaces for lithium-ion batteries. (20th October 2018) - Chen, Hedong; Wang, Shaofeng; Liu, Xiaojing; Hou, Xianhua; Chen, Fuming; Pan, Hui; Qin, Haiqing; Lam, Kwok-ho; Xia, Yingchun; Zhou, Guofu
Abstract: The double-coated Si-based composite (nano-Si@carbon@void@graphene sheets) with the excellent electrochemical properties have been successfully designed and prepared via a spray drying method. The composite electrode at 0.1 A g −1 presents a high initial discharge/charge capacity of 2744.9/2389.8 mAh g −1, representing high initial coloumbic efficiency of 87.1%. After 200 cycles, a high charge capacity of 1325.2 mAh g −1 is obtained. Even at 0.8 A g −1 and 1.6 A g −1, the composite electrode still maintain high capacities of 1466.1 mAh g −1 and 561.5 mAh g −1, respectively. The enhanced performance is mainly attributed to the double-coated structure with void space resulting from the carbon layer and wrinkled graphene sheets. The three-dimensional network structure from carbon shell and graphene is capable of improving the electrical conductivity of the composite, buffering the significant volume expansion due to the intercalation and deintercalation of lithium-ions on the Si-based electrode, providing accommodation space for the volume changes and diffusion paths for lithium-ions. Furthermore, the part amorphous structure derived from the nano-silicon exhibits a cushioning effect on the electrode structure during the discharge/charge process of lithium-ion batteries. Graphical abstract: Highlights: Double-coated Si composite is prepared. Amorphous Si exhibits cushioning effect. Double-coated structure shows excellent properties.